Production and characterization of mead from the honey of Melipona scutellaris stingless bees - Silva, Samira Maria Peixoto Cavalcante (2018)
The Institute of Brewing & Distilling Mead is a traditional alcoholic beverage obtained by fermenting must and can offer a solution to honey over-production and a way of valorizing honey of lower quality. The purpose of this study was to produce and characterize mead with different levels of sugars and alcohol obtained from honey from Melipona scutellaris. The honey used for mead preparation was analysed in order to ensure that it met the required quality standards. It was found that the alcoholic content and volatile acidity were outwith the limits established by Brazilian law. Mead legislation is based on the product obtained from Apis mellifera (‘honey bee’) honey and these results indicate the need to re-evaluate the standards established for this product in order to incorporate mead produced from honey from stingless bees of the genus Melipona. Copyright © 2018 The Institute of Brewing & Distilling.